1976
DOI: 10.1111/j.1751-0813.1976.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Preweaning Mortality in the Pig

Abstract: Preweaning mortality was studied in 34 commercial piggeries on the North Coast of New South Wales during a 12-month period. For the 1,068 farrowings recorded, the mean litter size at birth was 10.4 and 0.6 piglets per litter were stillborn. The mean total mortality to weaning was 19.7%, but for individual herds the figure varied from 5.1 to 48.2%. A number of biological factors influenced the extent of preweaning mortality. Most losses (74.6%) occurred during the first 4 days of life. The mortality increased s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…We observed a mortality of 20% before the age of 2 months. This level is comparable to veteri nary studies which also report causes of death similar to those observed here [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We observed a mortality of 20% before the age of 2 months. This level is comparable to veteri nary studies which also report causes of death similar to those observed here [1][2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 77%
“…In addition, they have a rapid rate of reproduction and can be approached easily providing the possibility of close clini cal observation. Veterinary studies would sug gest that a portion of the early mortality occurring in this species is unexplained [1][2][3][4][5][6]. We therefore conducted a prospective study to determine whether piglets present a pathol ogy which is comparable to SIDS in human beings.…”
Section: Introductionmentioning
confidence: 99%
“…Over half of piglet losses have been reported to occur in the first 2 to 3 d after birth (Bauman et al 1966;English and Smith 1975;Glastonbury 1976), and presumably a sizeable percentage of these deaths occur during the farrowing process itself. This might help to explain how a treatment imposed for a relatively short period (only until the last gilt in the room had finished farrowing) had such an impact on total pre-weaning mortality.…”
Section: Discussionmentioning
confidence: 99%
“…It may occur in both piglets and young pigs (3) and as many as 2% of the population may die from this (8). E. coli is the most common cause, but also another alpha-gal epitope expressing bacterium, Klebsiella pneumoniae, is a common cause (13,21). In the pig, all components of the native and the acquired immune systems develop in utero and are functional at birth, although less efficient (15).…”
Section: Health Protection In Xenograft Donor Pigsmentioning
confidence: 99%